Muscular dystrophies related to the cytoskeleton/nuclear envelope. - Nowak, K; McCullagh, K; Poon, E; Davies, K (2005)
Mutations in genes encoding proteins expressed in skeletal muscle cause a significant number of human diseases. Neuromuscular diseases are often severely debilitating for affected individuals, frequently leading to a shortened life span. Identifying the cause of these muscle diseases has provided insight not only into disease pathogenesis and muscle dysfunction, but also into the normal function of muscle. In 1987, dystrophin became the first disease-related human gene to be identified by positional cloning. Dystrophin is an integral component of the membrane-attached cytoskeleton of muscle fibres, with mutations in this gene causing Duchenne and Becker muscular dystrophy. One group of proteins known as the dystrophin-associated protein complex (DAPC), is believed to provide a molecular link between the actin cytoskeleton and the extracellular matrix in muscle cells, thereby sustaining sarcolemmal integrity during muscle contraction. Mutations in many members of the DAPC cause a variety of diseases, emphasising the importance of these genes. Another group of important proteins in skeletal muscle is the intermediate filament family, which provides mechanical strength and a supporting framework within the muscle cell. They anchor actin thin filaments through their expression at the Z-disk in sarcomeres, which in turn interact with myosin thick filaments to cause muscle contraction. This chapter will explore the protein components of the DAPC and the intermediate filament complex, highlighting a novel protein, which links the two, syncoilin. Human diseases and studies of existing animal models caused by mutations in these genes will also be described.